Gender, caste, and public goods provision in Indian village governments - Gajwani, Kiran; Zhang, Xiaobo (International Food Policy Research Institute, 2008)
This paper seeks to contribute to the literature on village governance and local public goods provision. Using data from 144 village-level governments in India's Tamil Nadu state, we examine whether the gender and caste of village government leaders influence village public goods provision. In particular, we examine: 1) whether public goods are provided in accordance with gender or caste preferences; and 2) whether public goods provision differs based on the knowledge level of the village government leader. We find evidence of different preferences for public goods between men and women, and between Scheduled Caste (SC) and non-SC persons. Additionally, a test of knowledge regarding the village government reveals that female and SC presidents receive lower scores relative to male and non-SC presidents, with women scoring lowest overall. We find that preferences and knowledge have little effect on public goods provision by female presidents, and hypothesize that this may be due to the influence of their male spouses. In the context of SC presidents, we find evidence that SC presidents provide more drinking water access-a location-specific public good-to SC-inhabited village areas.